Effects of Bicarbonate Stress on Serum Ions and Gill Transporters in Alkali and Freshwater Forms of Amur Ide (Leuciscus waleckii) - Chang, Yu Mei; Zhao, Xue Fei; Liew, Hon Jung; Sun, Bo; Wang, Shuang Yi; Luo, Liang; Zhang, Li Min; Liang, Li Qun (Frontiers in Physiology, 2021)
The Amur ide (Leuciscus waleckii) is a fish in the Cyprinidae family. Compared with other Amur ide living in freshwater ecosystems, the Amur ide population in Lake Dali Nor of China is famous for its high tolerance to the alkaline conditions of 54 mM (pH 9.6). Yet, surprisingly, the ionoregulatory mechanism responsible for this remarkable alkaline adaptation remains unclear. Therefore, this study sought to investigate how bicarbonate affects the acid-base balancing and ionoregulatory responses of this animal. Here, using a comparative approach, the alkali form of Amur ide and its ancestral freshwater form living in other freshwater basins were each exposed to 50 mM (pH 9.59 ± 0.09), a level close to the alkalinity of Lake Dali Nor, and their physiological (AE1) adjustment of ions and acid-base regulation were investigated. This study highlighted differences in blood pH and serum ions (e.g., Na+, K+, Cl−, and Ca2+), Na+/K+ ATPase (NKA) activity and its mRNA level, and mRNA expression of gill transporters (Na+/H+ exchanger member 2 and/or 3, Na+/HCO3- cotransporter (NBC1), Cl−/HCO3- exchanger, Na+/Cl− cotransporter (NCC), Na+/K+/2Cl− (NKCC1), SLC26A5, and SLC26A6) for alkalinity adaptation between the two forms of Amur ide differing in alkalinity tolerance. Specifically, close relationships among the serum Na+ and mRNA levels of NCC, NKCC1, and NHE, and also NKA and NBC1, in addition to serum Cl− and bicarbonate transporters (e.g., SLC26A5 and SLC26A6), characterized the alkali form of Amur ide. We propose that this ecotype can ensure its transepithelial Cl− and Na+ uptake/base secretions are highly functional, by its basolateral NKA with NBC1 and apical ionic transporters, and especially NCC incorporated with other transporters (e.g., SLC26). This suggests an evolved strong ability to maintain an ion osmotic and acid-base balance for more effectively facilitating its adaptability to the high alkaline environment. This study provides new insights into the physiological responses of the alkaline form of the Amur ide fish for adapting to extreme alkaline conditions. This information could be used as a reference to cultivating alkaline-tolerant fish species in abandoned alkaline waters.